Perilaku Pengunjung Ruang Publik Kawasan Masjid Nurul Bahri dengan Metode Place Center Mapping - Nurmiah; Karim, Febriyanti; Indriani Umar; Putri Ali (Universitas Negeri Gorontalo, 2025)
Nurul Bahri Mosque possesses strong potential as a public open space, supported by its scenic offshore coastal view that enhances the visual quality and attractiveness of the area. The mosque courtyard and surrounding open space function multifunctionally, accommodating religious, social, and recreational activities through pedestrian pathways that encourage visitor movement and interaction. However, many of these activities are not yet supported by adequate infrastructure, resulting in the suboptimal performance of the mosque courtyard’s dual role as both a place of worship and a tourism-oriented public space. This study examines the formation of activity spaces within the public open space of the Nurul Bahri Mosque by analyzing the relationship between spatial characteristics and visitor behavior. The research employs a behavioral approach using a system mapping technique, conducted objectively based on the time and spatial position of observed activities, applying Place-Centered Mapping and Person-Centered Mapping. The findings indicate that visitor behavior generates natural and context-driven activity patterns. No significant transformation of spatial dimensions is observed; however, variations in space utilization emerge across zones. Zone 2 shows distinctive activity patterns influenced by fishing activities and coastal proximity but lacks supporting street furniture, while Zone 3 accommodates core and supporting activities, including pedestrian crossings, without adequate infrastructure. These findings provide a basis for future spatial planning and facility development within the mosque area.